(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The development and the effectiveness of 5p’s in marketing strategies. These five are: people, product, place, promotion, and price. The 5p’s are key marketing elements designed to help you think about your business strategically that aims to build your business in a consistent way. The effectiveness of 5ps in marketing strategies can be asked to the entrepreneurial students for their business in school if the marketing strategies to be used are effective to the customer. The 5ps can help you to meet in the needs of your customer and to grow your business. The study used descriptive research design as best suited for investigation and achieve the purpose of the study. It focuses on the effectiveness of grade 12 Accountancy and Business Management students. There are five variables to be identified the effectiveness of having 5ps in marketing management. such as people, product, place, promotion, and price. Data were collected by distributing questionnaires to the 50 selective Grade 12 Accountancy and Business Management students. The results of the study revealed that true some extent, the effectiveness of 5ps as a basis for marketing strategies on selected grade 12 Entrepreneur ABM students of Bestlink College of the Philippines S.Y. 2018 –2019 in terms of (1) people -the knowing of wants and needs of the customer was the most effective in terms of People. (2) product -that the customer wants the product that a good quality.(3) place -that the product must be suitable in school are can affect to the very effectiveness in term of place.(4) promotion -that the most effective in promoting is using Facebook in promoting.(5) price -that the most effective strategy in marketing is the price should be affordable in term of price. The result demonstrates the needs for the teachers and school administrators to not just guide the Bestlink students, but also to encourage and inspire them. Parents need to motivate their child and encourage them to be successful in life. Most of the entrepreneur students use this 5ps in marketing strategy, for customer to be satisfied with their product and encourage them to buy the product. The students customers believe that the product must have good quality and price should be affordable compared the other product.